Co-amorphous solid dispersion systems of lacidipine-spironolactone with improved dissolution rate and enhanced physical stability - Zhaomeng Wang; Mengchi Sun; Tian Liu; Zisen Gao; Qing Ye; Xiao Tan; Yanxian Hou; Jin Sun; Dun Wang; Zhonggui He (Elsevier, 2019)
Co-amorphous solid dispersion (C-ASD) systems have attracted great attention to improve the solubility of poorly soluble drugs, but the selection of an appropriate stabilizer to stabilize amorphous forms is still a huge challenge. Herein, C-ASD system of two clinical combined used drugs (lacidipine (LCDP) and spironolactone (SPL)) as stabilizers to each other, was prepared by solvent evaporation method. The effects of variation in molar ratio of LCDP and SPL (3:1, 1:1, 1:3, 1:6, and 1:9) on the drug release characteristics were explored. Polarized light microscopy (PLM), powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were employed to evaluate the solid states. Prepared C-ASDs were further studied for their stability under the high humidity (RH 92.5%). Further analysis of C-ASDs via Fourier-transform infrared spectroscopy (FTIR) and Raman spectroscopy confirmed that hydrogen bond interactions between the two drugs played a significant role in maintaining the stability of the C-ASDs systems. Moreover, molecular dynamic (MD) simulations provided a clear insight into the stability mechanism at the molecular level. This study demonstrated the novel drug-drug C-ASDs systems is a promising formulation strategy for improved dissolution rate and enhanced physical stability of poorly soluble drugs. Keywords: Co-amorphous solid dispersion, Lacidipine, Spironolactone, Stability, Molecular dynamic (MD) simulations